Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Hydrochlorothiazide and Losartan Potassium in Tablet Dosage Form - Hossen, Md Arif; Haque, Md Ahsanul; Dewan, Irin; Kabir, ANM Hamidul; Hossain, Md Khalid; Islam, SM Ashraful (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In the present study, a simple, sensitive and specific liquid chromatography (RP-HPLC) method has been developed and validated for the quantification of hydrochlorothiazide and losartan potassium in tablet dosage form. A shim-pack CLC-ODS column (250 mm X 4.6 mm, 5μ and a mobile phase constituting 0.025 M phosphoric acid solution: acetonitrile (60:40 v/v, pH 3.0 adjusted with 80% phosphoric acid) were used. The flow rate was 1.5 ml/min and detection was carried by using ultraviolet (UV) detector at a wavelength of 254 nm. The retention times of hydrochlorothiazide and losartan potassium were 3.748 min and 8.790 min, respectively. The peaks of hydrochlorothiazide and losartan potassium were well separated (resolution 22.17). The calibration curves were linear over the concentration range of 80% to 120% (R2 > 0.999 for both the drugs). The proposed method is accurate with 100.165% recovery for hydrochlorothiazide and 100.422% recovery for losartan potassium and precise (% RSD < 0.5). The proposed method was successfully applied for the estimation of hydrochlorothiazide and losartan potassium in market products (three brands) and potency was found within limit. Therefore, this method can be a convenient and efficient option for the analysis of hydrochlorothiazide and losartan potassium in tablet dosage form. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10013 DUJPS 2011; 10(1): 35-42